A COMPARATIVE STUDY OF CALLIGRAPHY LEARNING IN MODERN AND TRADITIONAL BOARDING SCHOOLS - Putriani Dalimunthe; Tengku Sinar Mawanda; Ruwiyah Zamzam (Yayasan Haiah Nusratul Islam, 2024)
Calligraphy is a work of art that is currently being studied, especially in Islamic boarding schools, both at modern Islamic boarding schools and traditional Islamic boarding schools. This research is to find out the comparison of learning Calligraphy at Modern and Traditional Islamic Boarding Schools. The difference between learning Calligraphy Science this time The researcher took one of the huts as a comparison, namely the Modern Darussalam Gontor Islamic Boarding School and the Sabilul Mukminin Traditional Islamic Boarding School. This time the research method used for researchers is a descriptive approach through a qualitative approach and researchers also use literature reviews or collect data from various sources. This study also uses an interview approach, where researchers can collect various data from respondents. The results obtained from this study are that modern Islamic boarding schools prioritize learning calligraphy compared to traditional Islamic boarding schools.